A comparative study between extended aeration system and hi-kleen system - Chong Khai Lin (School of Environmental Engineering , University Malaysia Perlis, 2010)
Two sewage treatment plants (STP) were investigated over a 2 months period in order to measure the microbiological load of untreated municipal wastewater and to evaluate the removal efficiencies of different treatment systems. The STP investigated can be classified into smaller plants with enhanced secondary treatment. The plants studied had a considerable quantitative impact on the marine of the area. Consequently, it was anticipated that the microbiological load of the effluent would also be significant and also the e-coli that achieved the highest exceeding value for Perlis. Sixteen samples were taken from the influent and effluent of the STP, regardless of weather conditions, and e-coli was analyzed.